Joglars, música i entreteniment en els banquets medievals. - FERNÀNDEZ-CLOT, ANNA (Scripta)
The presence of minstrels, music and courtly entertainment is a cliché in the literary description of banquets and aristocratic celebrations in the Middle Ages. This paper collates and analyses the descriptions pictured both in stories and novels written in Occitan and Catalan between the 13th and the 15th centuries, as well as in royal chronicles and memorialistic literature from the 14th and 15th centuries. We will see which are the general characteristics of the cliché of the minstrels' perfomance in courtly banquets, as well as the development and adaptation of this cliché based on the type of text in which it is presented and on the evolution of the courtly entertainment.